Hemoglobin, anemia, and clinical outcomes in vericiguat global study in subjects with heart failure with reduced ejection fraction (VICTORIA). (14th October 2021) - Ezekowitz, J.A; Zheng, Y; Cohen-Solal, A; Melenovsky, V; Escobedo, J; Butler, J; Hernandez, A.F; Lam, C.S.P; O'Connor, C.M; Pieske, B; Ponikowski, P; Voors, A.A; et al.
Abstract: Background: In the VICTORIA trial of patients with HFrEF after a worsening HF event, anemia occurred more often in patients treated with vericiguat (7.6%) compared with placebo (5.7%). We explored the association between vericiguat, baseline hemoglobin, and anemia and also whether hemoglobin was related to the benefit of vericiguat in HF. Methods: Anemia was defined as a hemoglobin <13.0 g/dL in men and <12.0 g/dL in women (WHO anemia). Adverse events reported as new anemia were also evaluated (AE anemia). We evaluated the risk-adjusted relationship between baseline hemoglobin (as both quartiles and continuous variable), hematocrit, and hematinic indices with the primary outcome (composite of cardiovascular death or heart failure hospitalization). Time-updated hemoglobin relationship was also examined. Results: Of 4812 patients with baseline hemoglobin data available, 1719 (35.7%) were WHO anemic; median hemoglobin was 13.4 g/dL (IQR 12.1 to 14.7 g/dL). In total, 1643 patients had WHO anemia at 16 weeks (of which 284 were new from baseline for vericiguat and 219 for placebo) and this occurred more often in the vericiguat group than the placebo group (P<.001). Subsequently, there was no further decline in hemoglobin over the 96 weeks of follow-up (Figure A). The ratio of hemoglobin/hematocrit remained constant and none of the hematinic indices including red cell density width, mean corpuscular volume, white blood cell or platelet counts changed over time. Overall, AE anemia occurred in 342 patients (7.1%) and was more frequent in those with a lower baseline hemoglobin (hemoglobin Q1: 184 [14.5%], Q2: 94 [7.9%], Q3: 40 [3.4%], Q4: 24 [2.1%]; p<.001). Whereas outcomes were associated, quartiles of baseline hemoglobin were not related to the treatment benefit of vericiguat (compared with placebo) for the primary outcome (Figure B). Additionally, analysis of the time-updated hemoglobin values revealed no association with the treatment effect of vericiguat (compared with placebo) on the primary outcome. Conclusions: Anemia was present at baseline in over one-third of patients in the VICTORIA trial and was generally mild. Lower hemoglobin was associated with greater frequency of clinical events. Although vericiguat modestly lowered hemoglobin by 16 weeks, this effect did not further progress nor influence the association of benefit of vericiguat. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): Merck & Co., Inc. and Bayer